2021
DOI: 10.1038/s41598-021-85186-6
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is a risk factor for intrahepatic cholangiocarcinoma progression associated with alterations of metabolic activity and immune status

Abstract: Body mass index (BMI) is well known to be associated with poor prognosis in several cancers. The relationship between BMI and the long-term outcomes of patients with intrahepatic cholangiocarcinoma (ICC) is incompletely understood. This study investigated the relationships of BMI with clinicopathological characteristics and patient outcomes, focusing on metabolic activity and immune status. The relationship between BMI and the maximum standardized uptake value (SUVmax) on fluorine-18 fluorodeoxyglucose (18F-FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…understood that NAFLD is a risk factor for the development of hepatocellular carcinoma, but one study found that NAFLD may increase the risk of CCA development [63]. This work is supported by other findings indicating that obesity may promote CCA progression, as indicated by larger tumor size and increased metastasis in obese CCA patients compared with normal weight counterparts [64]. Others have found that NASH, but not NAFLD, was a significant risk factor for CCA development and worse prognosis [65].…”
Section: Cholestasis and Cholangiopathies Associated With Nafld And Nashmentioning
confidence: 75%
“…understood that NAFLD is a risk factor for the development of hepatocellular carcinoma, but one study found that NAFLD may increase the risk of CCA development [63]. This work is supported by other findings indicating that obesity may promote CCA progression, as indicated by larger tumor size and increased metastasis in obese CCA patients compared with normal weight counterparts [64]. Others have found that NASH, but not NAFLD, was a significant risk factor for CCA development and worse prognosis [65].…”
Section: Cholestasis and Cholangiopathies Associated With Nafld And Nashmentioning
confidence: 75%
“…Therefore, we performed RNA sequencing to elucidate the genes regulated by JMJD6, which resulted in the identification of 171 candidate genes. Our institution has previously reported the impact of tumor immunology on cancer prognosis ( 12 , 25 , 26 ); thus, we focused on immune-related genes. We found that PD-L1 mRNA levels increased in response to JMJD6 knockdown, indicating that JMJD6 regulates PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, genus Ruminococcaceae can help reduce polysaccharide degradation and reverses dextran sodium sulfate to preserve intestinal barrier integrity ( Wang et al., 2019 ). Previous studies suggested that gut microbiota was associated with body weight ( Cuevas-Sierra et al., 2019 ), and obesity might be a risk factor for CCA progression and postoperative recurrence ( Merath et al., 2019 ; Zhou et al., 2020 ; Yugawa et al., 2021 ). There was evidence concerning the potential role of gut microbiota and probiotic-derived extracellular vesicles (EVs) on obesity via the modulation of inflammation, metabolism, and gut permeability ( Díez-Sainz et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%